2013
DOI: 10.1080/20786204.2013.10874333
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive knowledge and practice among HIV-positive women receiving antiretroviral therapy at a district hospital in KwaZulu-Natal

Abstract: Objectives: To determine the knowledge and use of contraceptives by HIV-positive women attending an ART clinic.Design: Observational descriptive cross-sectional study.Setting and subjects: Many human immunodeficiency virus (HIV)-positive South African women fall pregnant each year while receiving antiretroviral therapy (ART). In 2010, 2 056 women of childbearing age attended the ART clinic at a district hospital south of Durban. Between October 2010 and June 2011, data were collected using a validated question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Information on dual contraception was obtained during interactions with health providers and peer counsellors or mentor-mothers at PMTCT clinic visits and support groups. Similar findings were reported in South Africa, where knowledge about condoms was associated with condom use [ 38 ] and Nigeria, where dual contraceptive use was determined by the level of awareness on dual method. However, other studies have reported thatsocio-cultural factors influenced whether or not HIV-infected women would practice dual contraception despite being aware of the importance of dual contraception [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 83%
“…Information on dual contraception was obtained during interactions with health providers and peer counsellors or mentor-mothers at PMTCT clinic visits and support groups. Similar findings were reported in South Africa, where knowledge about condoms was associated with condom use [ 38 ] and Nigeria, where dual contraceptive use was determined by the level of awareness on dual method. However, other studies have reported thatsocio-cultural factors influenced whether or not HIV-infected women would practice dual contraception despite being aware of the importance of dual contraception [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 83%
“…The most common form of contraception use by the respondents in the study was condom, femidom in 33.6 % of cases; the findings are consistent with other studies in HIV Clinics where condom was used due to easy accessibility and frequent exposure to counseling promoting condom use (16,20). Intra uterine contraceptive device (IUCD) was used by 30.3 % of the women, 29.4% used injectable contraceptives, 4.2 % used natural method of family planning while 2.5 % used pills, this contrasted studies done where majority of the respondents were using condom (21-23) and were using it consistently which may be due the fact that condoms are the most common form of contraception available (24).…”
Section: Discussionmentioning
confidence: 94%